PRIBUMISASI ISLAM DALAM TAFSIR AL-AZHAR PADA QS. AT-TAUBAH AYAT 60 TENTANG MUSTAHIQ ZAKAT - Ariandini, Rafika (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2019)
One of the goals of zakat is to prosper Muslims. To achieve these objectives, the Qur'an guides the distribution of zakat, namely in the QS. At-Taubah verse 60. 8 groups are entitled to receive zakat, namely the destitute, poor, amil zakat, al-mu'allafah qulubuhum, ar-riqab, people who are in debt, fi sabilillah and ibnu sabil . In reality, there are still distributions of zakat that are not following these provisions, because there are people who are not included in the group mustahiq zakat, but he gets zakat. QS interpretation study is needed. At-Taubah verse 60 contextually, so that it can be used as a guide in the distribution of zakat in Indonesia. The theory used in this research is the theory of the Islamic Nativism (Pribumisasi Islam) of Gus Dur. The theory of Islamic Nativism tries to dialogue between universal meanings and civilizations outside of Arabia, in this case, namely Indonesia. With this theory of Islamic indigenization, the author tries to find universalism, cosmopolitanism, and indigenization in Hamka's interpretation of QS. At-Taubah verse 60 concerning mutahiq zakat. In Hamka's interpretation of QS. At-Taubah verse 60 about mustahiq zakat is indigenous of Islam. One of the natives found in the interpretation of Hamka is amil zakat, in Indonesia what is called amil zakat is divided into two, namely those appointed by the government and zakat committees formed by a group of Muslims, such as in the majlis talim, community organizations, schools, and offices.